2002
DOI: 10.1177/1359105302007001658
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Depression in African American Cancer Survivors: The Reliability and Validity of the Center for Epidemiologic Study—Depression (CES-D) Scale

Abstract: The Center for Epidemiologic Study-Depression (CES-D) Scale has been used to assess levels of depressive symptomatology in cancer survivors but has not been validated in African American cancer survivors. The current study assessed the reliability and validity of the CES-D in 216 African American cancer survivors. A Cronbach alpha was calculated to determine internal consistency reliability, and correlations were computed between the CES-D and other measure of mood states (Profile of Mood States-Short Form and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 27 publications
2
30
0
Order By: Relevance
“…Another limitation of the study is the low internal consistency produced by the depressive symptoms measure (CESD-10). While previous studies have used the CESD with an African American population and produced a more acceptable Cronbach’s alpha, 65,66 clinical research has found that African Americans may exhibit atypical depressive symptomology, 67 which may have influenced our results. In addition, this study’s use of the 10-item version of the CESD as opposed to the 20-item scale may have led to the less than desirable reliability.…”
Section: Discussionmentioning
confidence: 87%
“…Another limitation of the study is the low internal consistency produced by the depressive symptoms measure (CESD-10). While previous studies have used the CESD with an African American population and produced a more acceptable Cronbach’s alpha, 65,66 clinical research has found that African Americans may exhibit atypical depressive symptomology, 67 which may have influenced our results. In addition, this study’s use of the 10-item version of the CESD as opposed to the 20-item scale may have led to the less than desirable reliability.…”
Section: Discussionmentioning
confidence: 87%
“…The psychometric properties have previously been found to be consistent across age, sex, and ethnic subgroups~Radloff & Locke, 1986!. Numerous researchers~e.g., Brown, Brody, & Stoneman, 2000;Conerly, Baker, & Dye, 2002;Knight & McCallum, 1998;Letiecq & Koblinsky, 2003;McCallion & Kolomer, 2000! have used the CES-D to investigate mental health outcomes among African American populations and estab- & Trivette, 1984!…”
Section: Methodsmentioning
confidence: 98%
“…Items from the tension-anxiety and depression-dejection scales of both versions closely resemble DSM-IV-TR criteria, albeit with heavy emphasis on the cardinal features rather than across the gamut of symptoms. The depressiondejection scale of the POMS-65 has also correlated highly with the CES-D (0.63 [54]; 0.80 [55]), which, together with the SCL-90-R, offers the most comprehensive assessment of DSM criteria of PROMs reviewed here.…”
Section: Pomsmentioning
confidence: 96%